Morphological changes of tissues in teeth with incomplete formation of the root - M. Ya. Pishkovtsi (Zaporozhye State Medical University, 2012)
The group of extracted teeth with incomplete formation of roots was morphologically analyzed. The signs of hypoplasia of all tissue components that can cause disorders in the process of eruption of teeth and their retention were revealed in the result.